Typing Special Characters as a Key Skill for Linguists (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
Most linguists have to type special characters that are not available on an ordinary keyboard on a regular basis. Reflecting about the general problems involved in typing special characters, I review different solutions and argue that linguists should not only be able to type special characters on their computers, but that they should also have some basic knowledge about their technical aspects and know how to expand and customize them. In order to improve the training of young scholars, it is important to discuss special character typing more openly in linguistics, especially in the classroom and with doctoral students, sharing individual solutions openly.
Keywords: typing special characters; IPA; teaching linguistics; key skills